Missing compared to what? Revisiting heritability, genes and culture - Feldman, Marcus W. (Philos Trans R Soc Lond B Biol Sci, 2018)
Standard models for the determination of phenotypes from genes are grounded in simple assumptions that are inherent in the modern evolutionary synthesis (MES), which was developed in the 1930s, 1940s and 1950s. The MES was framed in the context of Mendelian genetic transmission enhanced by the Fisherian view of the way discretely inherited genes determine continuously quantitative phenotypes. The statistical models that are used to estimate and interpret genetic contributions to human phenotypes—including behavioural traits—are constructed within the framework of the MES. Variance analysis constitutes the main tool and is used under this framework to characterize genetic inheritance, and hence determination of phenotypes. In this essay, we show that cultural inheritance, when incorporated into models for the determination of phenotypes, can sharply reduce estimates of the genetic contribution to these phenotypes. Recognition of the importance of non-genetic transmission of many human traits is becoming ever more necessary to prevent regression to the debates of the 1970s and 1980s concerning policies based on genetic determination of complex human phenotypes. This article is part of the theme issue ‘Bridging cultural gaps: interdisciplinary studies in human cultural evolution’.